2013 IEEE International Instrumentation and Measurement Technology Conference (I2MTC) 2013
DOI: 10.1109/i2mtc.2013.6555467
|View full text |Cite
|
Sign up to set email alerts
|

WLS distribution system state estimator based on voltages or branch-currents: Accuracy and performance comparison

Abstract: This paper presents a comparison between the two main classes of Weighted Least Squares (WLS) state estimators used in distribution systems: state estimators based on node voltage state variables and estimators based on a state expressed in terms of branch-currents. In particular, the actual accuracy achieved for the estimated quantities by these estimators and their modified versions is analysed in details along with their performance, considering different types of real-time measure- ments (traditional or ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 18 publications
0
18
0
3
Order By: Relevance
“…It is easy to understand how a simple variable elimination can be performed from (14), writing one current as a function of the other incident ones. In fact, for each zero injection, a current can be expressed as a function of the other state variables and eliminated from the state.…”
Section: Proposed Method: State Vector Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is easy to understand how a simple variable elimination can be performed from (14), writing one current as a function of the other incident ones. In fact, for each zero injection, a current can be expressed as a function of the other state variables and eliminated from the state.…”
Section: Proposed Method: State Vector Reductionmentioning
confidence: 99%
“…In particular, two main classes of DSSE exist, based on two different choices of the underlying state vector: node voltage state estimators, NV-DSSEs (as in [7,13]) and branch current estimators, BC-DSSEs (as [8][9][10][11][12]). BC-DSSE is suitably designed to better keep into account the peculiar characteristics of distribution systems, as the radial or weakly meshed topology and the high r/x ratios, and it is usually faster with respect to those based on voltage state (see [14]). …”
Section: Introductionmentioning
confidence: 99%
“…After comparing two main types of WLS state estimators for distribution systems which based on node voltage state and branchcurrent state respectively, Ref. [8] concluded that branchcurrent estimators with the slack bus voltage as one of the state variables can give estimation accuracies comparable to the voltage ones.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been presented since state estimation was introduced in power systems [1][2][3][4][5]. Among them, the predominant approach is the weighted least squares (WLS) method [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…20 The details of forward-sweep algorithm can be found in [44,54]. 21 The BC-DSSE is presented by Mesut Baran in his paper [32] 25 26 In [58] and [59] the two SE formulations, i.e. NV-DSSE and BC-DSSE, are compared.…”
mentioning
confidence: 99%